I would like to prove the following result:

Let $\mathcal C$ be the cissoid of Diocles having equation $x(x^2 + y^2) = b y^2$, where $b > 0$. Let $O$ be its singular point and let $F$ be its focus$^*$. Then, for every point $P$ of $\mathcal C$, the following equality holds: $$(FP - OP)(FP + 3 OP) = OF^2.$$

I already know that $O = (0, 0)$ and $F = (4b, 0)$. Since $\mathcal C$ can be parameterized by $$P = \left ( \frac{b t^2}{1 + t^2}, \frac{b t^3}{1 + t^2} \right ) \qquad (t \in \mathbb R)$$ one could prove the result by computing the lengths of all the segments involved. Indeed, $$FP = \frac b {\sqrt{1 + t^2}} (4 + t^2) \qquad OP = \frac b {\sqrt{1 + t^2}} t^2 \qquad OF = 4b$$ from which it is easy to see that $$(FP - OP)(FP + 3 OP) = 16b^2 \qquad OF^2 = 16 b^2.$$

But this proof gives no insight on why the result should be true. So what I am looking for is a geometric proof of the result.

Thank you in advance for any contribution.

${}^*$ Recall that a non-singular point $F$ is said to be a focus of a curve $\mathcal C$ if two tangent lines having slopes $i$ and $-i$ can be drawn from $F$ to $\mathcal C$.


We can use the fact that the cissoid $\mathcal C$ is the inverse curve of the parabola $\mathcal C'$ having equation $x = b y^2$ with respect to the unit circle centered at its vertex $O$. Then, the focus $F$ of $\mathcal C$ is the inverse of the focus $F'$ of $\mathcal C'$, as shown in the following figure:

The cissoid and its inverse

Here $P$ is a point of the cissoid $\mathcal C$ and $P'$ its inverse on the parabola $\mathcal C'$.

By definition of inversion we have: $$OP \cdot OP' = 1 \qquad OF \cdot OF' = 1$$ and so by the secant-secant power theorem the points $P, P', F, F'$ belong to the same circle. Hence, $F'\widehat F P = P\widehat {P'} F'$ because they are angles subtended by the same arc $PF'$ at the circumference. Then also $O\widehat F P = O \widehat {P'} F'$, and of course $P\widehat O F = P'\widehat O F'$, from which it follows that the triangles $OFP$ and $OP'F'$ are similar. Therefore: $$\frac {FP} {F'P'} = \frac {OF} {OP'}.$$

Now we can write the equality in terms of $OP'$, $OF'$ and $F'P'$. First, $$OP = \frac 1 {OP'} \qquad OF = \frac 1 {OF'} \qquad FP = \frac{F'P' \cdot OF} {OP'} = \frac {F'P'} {OP' \cdot OF'}$$ then the equality becomes: $$\left ( \frac {F'P'} {OP' \cdot OF'} - \frac 1 {OP'} \right ) \left ( \frac {F'P'} {OP' \cdot OF'} + 3 \cdot \frac 1 {OP'} \right ) = \frac 1 {OF'^2}$$ which reduces to: $$(F'P' - OF')(F'P' + 3 OF') = OP'^2.$$

This final equality holds in any parabola as shown by Jack D'Aurizio in this answer.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.